Pitch-class prevalence in plainchant, scale-degree consonance, and the origin of the rising leading tone. Issue 5 (20th October 2019) - Parncutt, Richard
Abstract : The most common tones in Medieval plainchant were G and D; the least common, B. I propose that individual scale degrees differed in perceived consonance depending on the number of audible partials (harmonics) corresponding to scale degrees. The first ten harmonics of G correspond to scale degrees (G, D, B, F, A), but not those of B (B, F#, D#, A, C#). More consonant tones were sung more often and became more stable (reference pitches). Tones C and F ( fa ) were sung more often than B and E ( mi ). The melodic semitone became psychologically associated with a difference in stability.